Arabica Coffee Farmer Behaviour Model on Sustainability Coffee Farming In Bondowoso Regency : A Relationship Between Entrepreneurial Behaviour, Agricultural Business Of Management And Green Agriculture Practice - Weni Indah Doktri Agus Tapaningsih; Eko Soemarjono; Hosaini Hosaini (Social Science Academic, 2025)
This research is aim to know the relationship between entreprenerial behaviour, agriultural business of management and green agricuture practice on Agribusiness Arabica Coffee in Bondowoso Regency. This research is quantitative assosiative research. This research conducted 100 repondents of arabika coffee farmer java ijen raung in Bondowoso Regency.This research use purposive sampling technique. This study use Smart-PlS Anlysis. The result of this research is that Entrepreneurial Behaviour (EB) and Agriculural of Business Management (AM) have a significant influence on the success of Arabica Smallholder Coffee Farming (AS) in Bondowoso Regency and Entrepreneurial Behaviour (EB) and Agricultural of Business Management (AM) have no significant effect on the sustainability of Arabica smallholder coffee farming (ASUS) in Bondowoso regency.